An exploratory study on the mechanism of Huangqi Guizhi Wuwu Decoction in the treatment of neuropathic pain. Issue 2 (5th May 2022) - Luo, Bo‐Yan; Zhou, Hong‐Su; Xiao, Qiu‐Xia; He, Yu‐Qi
Abstract: Huangqi Guizhi Wuwu Decoction (HGWD) has a definite effect on neuropathic pain (NP), whereas the specific mechanism has not been elucidated. The components and targets in HGWD were collected and identified through System Pharmacology Database (Traditional Chinese Medicine Database and Analysis Platform). Genecards and Online Mendelian Inheritance in Man databases were used to search for NP‐related genes. The Venn diagram was drawn to get the intersection target. Cytoscape 3.8.0 software was used to construct the compound‐disease‐target‐pathway networks. STRING database was applied to analyze protein–protein interaction of potential targets. Kyoto Encyclopedia of Genes and Genomes (KEGG) and Gene Ontology (GO) analyses were used to identify the function of genes related to NP. Finally, molecular docking was performed to visualize the binding mode and affinity between proteins and active ingredients. According to the intersection target of the Venn diagram, the network graph is constructed by Cytoscape and the results show the five compounds, β‐sitosterol, (+)‐catechin, quercetin, Stigmasterol, kaempferol, and 15 genes (CASP3, FOS, GSK3B, HSP90AA1, IKBKB, IL6, MAPK8, RELA, ICAM1, SELE, ELK1, HSPB1, PRKACA, PRKCA, RAF1) were highly correlated with NP. KEGG and GO of 15 genes results that TNF, IL‐17 and MAPK signaling pathway were Significantly related to the pathological mechanism of NP. Molecular docking showed that core genes in this network were IL‐6 (TNF and IL‐17 signaling pathways), ICAM1 (TNF signaling pathway), and CASP3 (three signal pathways). This study found that the five active compounds, three core genes, and three signaling pathways may be the key to the treatment of NP by HGWD. Abstract : The intersection genes of Huangqi Guizhi Wuwu Decoction (HGWD) and neuropathic pain (NP) were analyzed by the Kyoto Encyclopedia of Genes and Genomes and Gene Ontology to obtain the relevant pathway network map, and then the key genes in the signaling pathway were molecularly docked to explain the potential effect of HGWD in the treatment of NP.